Identifikasi Unsur Pembentuk Karakter Langgam Arsitektur Klasik pada Bangunan Gereja Santo Mikael di Seminyak Bali - Anak Agung Gde Djaja Bharuna S (Jurnal Kajian Bali (Journal of Bali Studies), 2023)
St. Mikael's Church is one of the old churches located on Jalan Camplung Tanduk No. 66, Seminyak Kuta Bali. This church has historical value and classical architectural style that can be seen in the building's facade. This study aims to identify the elements forming the classical architectural style of the church, as an enrichment of insight into the classical architectural style of ancient buildings. Identification analysis is presented in the table of elements of the classical architectural style through a study of the elements forming the outside/exterior and inside/interior of the building. The research method used was descriptive analysis, with the stages of data collection, analysis, and drawing conclusions. Supporting data was done by direct literature study, observation, and documentation. The results of the study show that the St. Mikael significantly applies the classical architectural style, and the architectural elements that appear to be more dominant are ornaments, window shapes, columns, building facades, and interiors.